THE EFFECTIVENESS OF THE MARKET PLACE ACTIVITY LEARNING MODEL IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS IN SMP - Rusydi Ananda; Mohammad Al Farabi; Ahmadi Ahmadi (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2021)
This study discusses the effectiveness of the marketplace activity learning model in Islamic religious education subjects at Raudhatul Jannah Middle School, Subulussalam City, Aceh. The purpose of this study was to determine the concepts used in the marketplace activity learning model in Islamic religious education lessons, then to find out the implementation of the Market Place Activity Learning Model in Islamic Religious Education Subjects, and to determine the Effectiveness of the Implementation of the Market Place Activity Learning Model in Educational Subjects. Islam at Raudhatul Jannah Middle School, Subulussalam City, Aceh. The results of this study are: the concept of the marketplace Activity Learning Model starting with the PAI teacher explaining the subject and objectives to be achieved in learning about complex explanatory texts, film/drama review texts, and biographical retelling texts. The teacher educates students in terms of buying and selling through the materials that have been provided. Implementing the Market Place Activity Learning Model in PAI Learning at Raudhatul Jannah Junior High School Subulussalam City makes students more active in their class. The PAI teacher also pays more attention to students by increasing students' enthusiasm for learning. Market Place Activity learning model in PAI learning is very effective.